Characterization of two thymosins as immune-related genes in common carp (Cyprinus carpio L.). Issue 1 (May 2015) - Xiao, Zhangang; Shen, Jing; Feng, Hong; Liu, Hong; Wang, Yaping; Huang, Rong; Guo, Qionglin
Highlights Full cDNA sequences of two common carp thymosins have been identified. The expression patterns of common carp thymosin genes in different tissues and during embryogenesis have been determined. The transcriptional changes of carp thymosin genes after spring viraemia of carp virus (SVCV) infection have been detected. The expressions of T lymphocyte-related genes increased after transient over-expression of carp thymosins in zebrafish.